Federalism and the Political Inclusion of Indigenous Nationalities in Nepal’s Local Governance - Karki, Nani Maiya; Baral, Rameshor; Sapkota, Jagannath (International Research Journal of MMC, 2026)
Federalism in Nepal was introduced to promote inclusive governance and enhance the political participation of historically marginalized communities, including Indigenous Nationalities (Adivasi Janajati). The establishment of local governments has created new opportunities for Indigenous representation and participation in decision-making processes. This study examines the extent to which federal restructuring has contributed to the political inclusion of Indigenous Nationalities in Nepal’s local governance system. The chief objective of the study is to analyze the impact of federalism on the political inclusion and representation of Indigenous Nationalities in Nepal’s local governance by comparing the 2022 local elections. This study examines the political representation of Indigenous Nationalities in Nepal following the institutionalization of federalism. Using a qualitative approach and secondary data sources, it analyzes Indigenous participation in local elections, particularly the 2022 elections. The findings highlight the role of federal restructuring in enhancing political inclusion, representation, and empowerment within local governance structures.The study finds that Nepal’s federal system has increased the political representation of Indigenous Nationalities through constitutional inclusion and proportional electoral mechanisms. However, their participation remains uneven, with limited access to key leadership positions and continued dominance of non-Indigenous groups and males. Despite progress in ethnic recognition and local-level participation, structural and regional disparities still constrain meaningful political empowerment. This study is useful for policymakers and government institutions to strengthen inclusive policies and improve the effective implementation of federalism in Nepal. It also benefits researchers and scholars by providing empirical insights into Indigenous political representation and local governance dynamics.